What do i want? The effects of individual aspiration and relational capability on collaboration preferences - Schillebeeckx, Simon J. D.; Chaturvedi, Sankalp; George, Gerard; King, Zella (Strategic Management Journal, 2016)
Research summary: We examine individuals' collaboration preferences in the K nowledge T ransfer N etwork ( KTN ) for the UK plastics electronics sector. Using conjoint analysis, we investigate how aspiration gaps and relational capability affect the value placed on potential organizational collaborations. Aspiration gaps reflect individuals' perception of whether they are ahead of or behind peers on their career trajectory, and relational capability captures three distinct dimensions: networking skills, openness to collaborate, and network awareness. Our findings suggest that positive and negative aspiration gaps augment preferences to form organizational partnerships. These effects are positively moderated by networking skills and openness and negatively moderated by network awareness. We discuss the implications of these findings for theories of partnership formation, scientific collaboration, and behavioral strategy . Managerial summary: University–industry collaboration is important to the creation and application of new knowledge. Such collaboration requires individuals of different backgrounds to work together, which can be difficult. We investigate what drives individuals' preferences to collaborate. We find that individuals who consider themselves ahead of or behind their peers are more favorable toward collaboration. We also find that networking skill and openness augment this positive collaboration disposition whereas awareness of the network members makes one more selective and reduces the proclivity to collaborate . Copyright © 2015 John Wiley & Sons, Ltd.